The Challenges in Developing Efficient and Robust Synthetic Homing Endonuclease Gene Drives - Verkuijl, Sebald A. N.; Ang, Joshua X. D.; Alphey, Luke; Bonsall, Michael B.; Anderson, Michelle A. E. (Frontiers in Bioengineering and Biotechnology, 2022)
Making discrete and precise genetic changes to wild populations has been proposed as a means of addressing some of the world's most pressing ecological and public health challenges caused by insect pests. Technologies that would allow this, such as synthetic gene drives, have been under development for many decades. Recently, a new generation of programmable nucleases has dramatically accelerated technological development. CRISPR-Cas9 has improved the efficiency of genetic engineering and has been used as the principal effector nuclease in different gene drive inheritance biasing mechanisms. Of these nuclease-based gene drives, homing endonuclease gene drives have been the subject of the bulk of research efforts (particularly in insects), with many different iterations having been developed upon similar core designs. We chart the history of homing gene drive development, highlighting the emergence of challenges such as unintended repair outcomes, 'leaky' expression, and parental deposition. We conclude by discussing the progress made in developing strategies to increase the efficiency of homing endonuclease gene drives and mitigate or prevent unintended outcomes.